Cold sensitive engrams control whole-body thermoregulatory responses - Muñoz Zamora, Andrea (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2024)
Environmental thermal challenges trigger the brain to coordinate both autonomic and behavioral responses to maintain optimal body temperature. It is unknown how temperature information is precisely stored and retrieved in the brain, and how it is converted into a physiological response. Here, we investigated whether memories could control whole-body metabolism by training mice to remember a thermal challenge. Mice were conditioned to associate a context with a specific temperature, by combining thermoregulatory Pavlovian conditioning with engram labeling technology and optogenetics. We report that if mice are returned to an environment where they previously experienced a 4°C cold challenge, they increase their metabolic rates regardless of the actual environmental temperature. Additionally, we show increased hypothalamic activity when animals are exposed to the cold, and that a specific network emerges between the hippocampus and the hypothalamus during the recall of a cold memory. Moreover, both natural retrieval and artificial reactivation of cold-sensitive memory engrams in the hippocampus mimic the physiological responses that are seen during a cold- challenge. These results show that retrieval of a cold memory causes whole-body autonomic and behavioral responses that enable animals to maintain thermal homeostasis.
APPROVED
Keywords: Thermoregulation; Engrams; Memory; Whole-body metabolism; Brown Adipose Tissue